(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The article analyzes the experience of the Vigevano prison’s detained involved in the theater laboratory project envisaged in the "Educating yourself in legality" project. By exploring the self-reflexive practices and paths of biographical awareness of four detained-actresses, the article investigates the ways in which the theatrical activity contributed to the transformation of their daily practices, as well as of self-representation models.